0296 Vigilant Attention Performance Advantage Conferred by TNFα G308A Polymorphism is Associated with Diminished Delta and Theta Power in the Non-REM Sleep EEG. (25th May 2022) - Skeiky, Lillian; Finlay, Myles; Satterfield, Brieann; Schmidt, Michelle; Wisor, Jonathan; Van Dongen, Hans
Abstract: Introduction: Carriers of the A allele of a single nucleotide polymorphism of the TNFα gene (G308A, rs1800629) are relatively resilient to vigilant attention performance impairment from total sleep deprivation (TSD), as compared to G/G homozygotes, and even exhibit a small performance advantage at baseline. The mechanism underlying this effect remains unclear. As TNFα is a sleep regulatory substance, we investigated whether TNFα G308A genotype is associated with systematic differences in markers of sleep homeostasis. Methods: N=168 healthy young adults (ages 27.4±5.4y; 86 women) participated in one of seven in-laboratory TSD studies. During TSD, performance was assessed every 2–3h using a psychomotor vigilance test (PVT). The TSD period was preceded and followed by nocturnal sleep opportunities (baseline and recovery, respectively), which were recorded polysomnographically and scored according to AASM criteria. The EEG (C3-M2 derivation) of stages N2 and N3 non-REM sleep was investigated using spectral analysis. Results: The genotype distribution of the sample was 0.6% A/A, 26.8% A/G, 72.6% G/G, in Hardy-Weinberg equilibrium (P=0.14). As documented previously, A allele carriers, compared to G/G homozygotes, had fewer PVT lapses (RTs>500ms) at baseline and during TSD, indicating greater resilience to sleep deprivation. During both baseline and recovery sleep, A allele carriers, compared to G/G homozygotes, displayed reduced power in the delta (0.8–4.0Hz; P=0.017) and theta (4.2–8.0Hz; P=0.004) bands of the non-REM sleep EEG. Conclusion: The performance advantage of the A allele carriers brings to mind the "banking sleep" phenomenon previously observed in sleep deprivation studies with prior sleep extension, suggesting that the A allele carriers gained this advantage by essentially being able to bank sleep. If this interpretation is correct, then the diminished power in the delta and theta bands of the non-REM sleep EEG in the A allele carriers, which suggests reduced homeostatic sleep pressure during both baseline and recovery sleep, may imply that the A allele carriers operate at a lower homeostatic setpoint due to an underlying advantage in the recuperative efficiency of sleep. Support (If Any): NIH R01HL070154, R21CA167691, R01HL105768; ONR N00014-13-C-0063, N00014-13-1-0302, FAA DTFAAC-11-A-00003, CDMRP W81XWH-16-1-0319, USAMRDC W81XWH-05-1-0099, and an SRS Elliot D. Weitzman, M.D. Research Grant.